Effects of vascular infusion with a solution of sugars, sodium chloride, and phosphates plus vitamins C, E, or C+E on display color - Yancey, E.J.; Hunt, Melvin C.; Addis, P.B.; Katsanidis, E.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three groups of 12 (n=36) grain-finished, crossbred Charolais steers were humanely slaughtered, and nine in each group were infused via the carotid artery with an aqueous solution of sugars, sodium chloride, and phosphates plus either vitamin C, E, or C plus E. Three in each group served as noninfused controls. Vascular infusion improved redness of longissimus thoracis (ribeye) muscles at 24 hours postmortem, but had little effect on display color stability for steaks. Vascular infusion with the solutions containing vitamin E improved color panel visual evaluations of ground beef at 4 days simulated retail display.
Keywords: Beef; Vascular infusion; Color